Die verpleegonderwyser - Dié innovateur? - W. Kotzé (AOSIS, 1984)
We exist in a dynamically changing world which requires that we are able to adapt. The process of innovation is a complex one which must be approached scientifically and seen within the broad framework of the system as a whole. The ideal innovator is a person who has been scientifically prepared and has research ability. She must also be well-versed in and identify herself with the philosophy of the profession and the meaning of professionalism. Successful innovation can however only result from a well co-ordinated team effort, directed by nurses who know what they are doing and can account for their approaches and actions.